(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
Polygamy is an acceptable institution in African culture and Igboland, in particular. Its practice remained relatively composed until the early 20th century when Christian missionaries with the support of the British colonial rule, ignorantly, raised hammer against it in the area. This study investigated and observed that both the polygamy and monogamy in the area were respectively, associated with economic and social values that were accentuated by the tradition and culture of the people. These values were what the Europeans and Christian missionaries of different denominations and appellations failed to venerate in their various encounter with the Igbo, for instance. They attempted to eliminate polygamy through altering marriage rules and giving preferential and fondness treatments to monogamous men. It was equally, discovered that in doing so, numerous negative effects, namely; increasing rate of infidelity in marriage, such as adultery, and death, increase in number of illegitimate children, excessive concubinary game among men, increasing spread of sexually related diseases, among others, were left on the people. This study as well, observed that there is nothing wrong with polygamy. It is a matter of understanding the tenet, its practice and the parties involved. Either monogamy or polygamy is not relevant to Christian salvation. Of course, the bible did not recognize any of them as being sinful. The work relied on both primary and secondary sources. Its data were analyzed qualitatively according to contents.